2016
DOI: 10.1002/ange.201509864
|View full text |Cite
|
Sign up to set email alerts
|

Triazine‐Based Sequence‐Defined Polymers with Side‐Chain Diversity and Backbone–Backbone Interaction Motifs

Abstract: Sequence control in polymers,well-known in nature, encodes structure and functionality.H ere we introduce an ew architecture,b ased on the nucleophilic aromatic substitution chemistry of cyanuric chloride,t hat creates an ew class of sequence-defined polymers dubbed TZPs.Proof of concept is demonstrated with two synthesized hexamers,h aving neutral and ionizable side chains.M olecular dynamics simulations show backbone-backbone interactions,i ncluding H-bonding motifs and pi-pi interactions.T his architecture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Directly inspired by biologically accessible DNA systems—for example, nucleobase-coded chains—sequence-defined macromolecules have been synthesized employing template-based coding strategies26272829 or via the generation of regulated sequence alternating thymine hybrid polymers30, as well as the design of reactions with iterative protection/deprotection steps on supports3132. Further, bulk reactions have been conducted in flow systems based on iterative synthesis33.…”
mentioning
confidence: 99%
“…Directly inspired by biologically accessible DNA systems—for example, nucleobase-coded chains—sequence-defined macromolecules have been synthesized employing template-based coding strategies26272829 or via the generation of regulated sequence alternating thymine hybrid polymers30, as well as the design of reactions with iterative protection/deprotection steps on supports3132. Further, bulk reactions have been conducted in flow systems based on iterative synthesis33.…”
mentioning
confidence: 99%
“…Materials having a heterocyclic moiety such as a s-triazine ring in their backbone chain have acquired special attention as a result of the significant influence on the end-product properties [12][13][14]. The sophisticated structure of the s-triazine ring as well as the exceptional reactivity of the starting material cyanuric chloride (TCT) has been employed as a basic core for preparation of an enormous number of derivatives, as a result of its commercial accessibility and the three chlorine atoms can be exchanged by distinct nucleophiles with the control of temperature that make it valuable in material [15][16][17][18][19][20][21] and industrial applications [22][23][24][25]. Recently, many scientists reported that polymer-based s-triazine has been used in the design and advancement of fire-retardant derivatives [26][27][28], metal adsorption [29], carbon dioxide capture [30][31][32] and covalent organic frameworks [24,25,28].…”
Section: Introductionmentioning
confidence: 99%
“…In search of potential strategies to facilitate the synthesis of multifunctional homopolymers, we decided to explore the utility of 2,4,6-trichloro-1,3,5-triazine (TCT) for installing two reactive groups onto polymers for subsequent functionalization via straightforward nucleophilic aromatic substitution. Simanek and co-workers have extensively studied TCT for dendrimer synthesis, and the compound has also been employed in a number of other ways, including as immobilized reagents, nucleophile scavengers, PET imaging probes, targeting conjugates, porous materials, and sequence-defined polymers . TCT undergoes sequential nucleophilic aromatic substitution reactions at increasing temperatures because each substitution step decreases the reactivity of the triazine ring through loss of σ-bond electron withdrawal of a chlorine atom and gain of π-orbital electronic donation of added nucleophiles .…”
Section: Introductionmentioning
confidence: 99%
“…Simanek and co-workers have extensively studied TCT for dendrimer synthesis, 41−48 and the compound has also been employed in a number of other ways, including as immobilized reagents, 49 nucleophile scavengers, 50 PET imaging probes, 51 targeting conjugates, 52 porous materials, 53 and sequence-defined polymers. 54 TCT undergoes sequential nucleophilic aromatic substitution reactions at increasing temperatures because each substitution step decreases the reactivity of the triazine ring through loss of σ-bond electron withdrawal of a chlorine atom and gain of π-orbital electronic donation of added nucleophiles. 55 TCT's controlled electrophilicity thus allows chemoselective and sequential functionalization that parallels previous multifunctional polymer synthesis techniques, yet can accommodate a broad scope of readily available nucleophiles.…”
Section: ■ Introductionmentioning
confidence: 99%